Social agency in contemporary international ceramics - Manar Munir Mohamed; Rula Abdul-Ilah Alwan Al-Nuaimi (الاكاديمي)
Effectiveness is the main criterion for evaluating any work of art, as it is embodied in the creative process through which the artist seeks to achieve aesthetic, functional or symbolic goals. This event has been associated with man since ancient times, as different civilizations sought to express themselves and their creations through the arts. One of the most prominent examples of this event is ceramics, as it has evolved over the ages, from being a traditional craft to becoming a contemporary art that is of great interest in the global art scene. This development has contributed to the diversity of techniques and forms of expression used by potters, which has complicated the visual text of ceramic works and increased their impact on the recipient. The potters focused on different artistic elements (such as material, shape, technique and color) to deliver their artistic messages and achieve their creative goals. Where the study deals with the relationship between the effectiveness in the art of ceramics and the developments witnessed by this art